PENGARUH PENGGUNAAN MODEL PEMBELAJARAN READ – ANSWER – DISCUSS – EXPLAIN – CREATE (RADEC) TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Aidatul Fitria, Laili; Setiyawati, Enik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the effect of RADEC learning model on science literacy skills of elementary school students. The research used is quantitative research with pre-experimental method in the form of One Group Pretest Posttest Design, which uses one experimental class at SDN Banjarsari. The population in this study were all third grade students of SDN Banjarsari, totaling 21 students. Sanpel was selected using saturated sampling technique. The data collection technique in this study was through the test method, namely pretest and posttest. The instrument used in this study is a test with valid and reliable literacy questions to measure the level of science literacy skills of students who have been validated by two experts in their fields. The data analysis technique in this study used the N - Gain test and paired sample t - test. Based on the results of the t-test that the sig. 2 tailed of 0.000 <0.05, meaning that there is an effect of RADEC learning model on the science literacy skills of grade III elementary school and obtained the average N-Gain score of 0.48 with a moderate category that there is an effect of RADEC learning model on the science literacy skills of grade III elementary school students of SDN Banjarsari in the moderate category. Keywords: elementary school, RADEC learning model, science literacy